2004
DOI: 10.1186/1471-2431-4-15
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Retinopathy of Prematurity with topical ketorolac tromethamine: a preliminary study

Abstract: Retinopathy of Prematurity (ROP)KetorolacCryotherapyPreterm newbornsnon-steroid anti-inflammatory drugs (NSAIDS). AbstractBackground: Retinopathy of Prematurity (ROP) is a common retinal neovascular disorder of premature infants. It is of variable severity, usually heals with mild or no sequelae, but may progress to blindness from retinal detachments or severe retinal scar formation. This is a preliminary report of the effectiveness and safety of a new and original use of topical ketorolac in preterm newborn t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Upon topical application, ketorolac diminishes prostaglandin E 2 concentration in aqueous humor [ 74 ]. A recent preliminary report suggests that ketorolac in the form of an ophthalmic solution can reduce the risk of developing severe ROP in very preterm newborns, without producing significant adverse side effects [ 75 ]. Interestingly, the authors showed that the incidence of severe ROP was significantly lower in very preterm newborns treated with ketorolac, when compared to the controls not receiving such treatment.…”
Section: Retinopathy Of Prematurity (Rop)mentioning
confidence: 99%
“…Upon topical application, ketorolac diminishes prostaglandin E 2 concentration in aqueous humor [ 74 ]. A recent preliminary report suggests that ketorolac in the form of an ophthalmic solution can reduce the risk of developing severe ROP in very preterm newborns, without producing significant adverse side effects [ 75 ]. Interestingly, the authors showed that the incidence of severe ROP was significantly lower in very preterm newborns treated with ketorolac, when compared to the controls not receiving such treatment.…”
Section: Retinopathy Of Prematurity (Rop)mentioning
confidence: 99%
“…Oxygen therapy was administered for a substantially longer duration in the control group. This suggests that ketorolac in the form of an ophthalmic solution can reduce the danger of developing severe ROP in very preterm newborns, without producing substantial adverse effects …”
Section: Ketorolac In Childrenmentioning
confidence: 99%
“…Caffeine citrate, which is used worldwide and is standard of care for AOP [143, 144] has been shown to have antioxidant properties [145], to significantly reduce the incidence of severe ROP [146], and to normalize aberrant retinal proteomic profiles in OIR [147]. Non-steroidal anti-inflammatory drugs (NSAIDs) have also been shown to reduce the incidence of ROP [148]. Caffeine and NSAID synergism was protective against severe OIR using our IH/IHR model [139].…”
Section: Discussionmentioning
confidence: 99%